2018
DOI: 10.1039/c8cp00396c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the micelle structure of oleic acid-based gemini surfactants: effect of stereochemistry

Abstract: In this study, we synthesize a novel oleic acid-based gemini surfactant with carboxylate headgroups, and study the effect of stereochemistry (anti- vs. syn-) on self-aggregation properties in water. We investigate these properties using phase diagrams, static surface tension, and one-dimensional and two-dimensional nuclear magnetic resonance (NMR) measurements. We find that a phase transition from a hexagonal liquid crystal (H1) phase to a lamellar liquid crystal (Lα) phase occurs at a lower surfactant concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Concerning Γ max and A min values of the three gemini surfactants, it is interesting to note that SELD gave the slightly higher Γ max value and lower A min value when compared with SBLD, suggesting a more densely packing of SELD at the water‐air interface. This may be caused by a different composition of the regioisomers for the synthesized sulfonate gemini surfactants (Figure S2), which is similar in accordance with previous literature focusing on the effect of stereochemistry of gemini surfactants on their interfacial properties and self‐aggregation properties in water 29 . Further evidence from extensive experimental studies is required to verify this.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Concerning Γ max and A min values of the three gemini surfactants, it is interesting to note that SELD gave the slightly higher Γ max value and lower A min value when compared with SBLD, suggesting a more densely packing of SELD at the water‐air interface. This may be caused by a different composition of the regioisomers for the synthesized sulfonate gemini surfactants (Figure S2), which is similar in accordance with previous literature focusing on the effect of stereochemistry of gemini surfactants on their interfacial properties and self‐aggregation properties in water 29 . Further evidence from extensive experimental studies is required to verify this.…”
Section: Resultssupporting
confidence: 86%
“…This may be caused by a different composition of the regioisomers for the synthesized sulfonate gemini surfactants (Figure S2), which is similar in accordance with previous literature focusing on the effect of stereochemistry of gemini surfactants on their interfacial properties and self-aggregation properties in water. 29 Further evidence from extensive experimental studies is required to verify this. As is shown in Table 3, we also note that the calculated ΔG 0 ads values of the synthesized sulfonate gemini surfactants are always negatively larger than the corresponding ΔG 0 mic values, indicating that the adsorption occurs predominantly over the micellization that is seen in aqueous solution.…”
Section: Equilibrium Surface Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already studied the interfacial properties and self-aggregation structures of a carboxylate-type gemini surfactant synthesized from oleic acid ( anti -CC-9,9-EsH10-Na, Figure ). We found that this surfactant showed excellent interfacial activity and solubility in water, as generally observed in gemini surfactant systems. Additionally, this surfactant yielded highly ordered α-gels in the presence of 1-tetradecanol (C 14 OH) even at high water concentrations . In this work, we studied the structural changes in the α-gel bilayers and domains induced by temperature and shear flow in the anti -CC-9,9-EsH10-Na/C 14 OH/water system.…”
Section: Introductionmentioning
confidence: 86%
“…Micelles functionally facilitate the absorption of water-insoluble fat and fat-soluble vitamins [80]. Their size is normally within in a range between 5 and 100 nm; amphiphilic molecules consist of a core: hydrophobic fragments and shell and hydrophilic moieties [81]. Water-insoluble drugs are usually intravenously administrated with an adjuvant solubilizing agent such as ethanol, which mainly has common toxic side effects [82].…”
Section: Pluronic Micellesmentioning
confidence: 99%